Tree Species Diversity at Nampui National Protected Area, Namon Village, Thongmixai District, Xayabuly Province - PHANTHVONG, Phitsanou; NANTHAVONG, Khamseng; NAMSENA, Montha; PAOTHOR, Viengsy; THAMMAVONG, Viengsamone; PHENGVICHITH , Vansaleum; BOUTTHAVONG, Saykham (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Study tree species diversity at Nampui National Protected Area, Namon Village, Thongmixai District, Xayabuly Province in 2024 with its objectives were to access the tree species diversity The diameter of the big tree is more than 10 Centimeters, important diversity index and evenness index. The methodlology were reviewing theory and field survey. The field survey were used the Relvé to survey plant population (Rawat, 2008). as simples plot construction of totally 52 pllos of the area of 2.08 hectares of the area of 175.66 hectares 1.118 as lower than 3% according to (Reif, 2012). included size of 20x20 m (big trees diameter 10 cm), The results of study found that all 52 survey plots with the area of 20,800 square metres having the totally 605 trees, 68 species, 29 families and 41genera, mostly was FABACEAE family (11 species, 103 trees), DIPTEROCARPACEAE family (9 species, 74 trees) respectively were MORACEAE family (6 species, 75 trees), MELIACEAE family (6 species, 59 trees), EUPHORBIACEAE family (4 species, 25 trees) and other families The important value index of standing trees (Species diversity) according to diversity index of Shanon-wiener (H′) was upto 3.96 Margalef Index (R1) up to 10.46 and Menhinick Index (R2) upto 2.76 of the the trees species at high grade indicated that having species diversity. Evenness Index: E equal to 0.929 indicated that tree species in the area having high evenness index. Important value index of standing tees found Gmelina arborea having important value index more (IVI) equal to 10.27%.